Paglubog ng araw: a short feature film - Bodios, Vanessa Angela C. (Animo Repository, 2018)
Paglubog ng araw is about Mikoy, an innocent boy who wanted to be a policeman when he grows up. He lived in a neighborhood where extrajudicial killings are frequent. He questioned the reason for those killings as he tried to understand the world he lives in. His mother Rosa did her best to protect him from dangers of the world, and made sure that he is at home before the sun sets. The film is a 15-minute short feature telling a story about one of the collateral damage of this campaigns inspired by the story of the four-year-old Althea Barbon who also wanted to be a policewoman in the future, just like Kian Delos Santos, and was felled by bullet that was meant for her father who was a suspected drug dealer. The production team of Paglubog ng araw was discerned that some people are pro-EJK. However, those people have not fully understood and are not knowledgeable of the fact that the lives taken were not only those of the alleged drug addicts, but also innocent lives, such as Kian and Althea-- the youth who could have contributed to making the Philippines a better place. Paglubog ng araw is a drama film that represents the innocent lives that could have been seeds of hope and justice for the future and got caught and killed in the middle of crossfires. It will project the contrast of the life and innocence of Mikoy and of death that nips the bud of Mikoy's hopes and dreams, and most especially, his life. The death of Mikoy was emphasized to further point out the purpose of this project-- to humanize the number of thousands of lives lost ever since this #WarOnDrugs started in 2016, and to inform with emphasis that among those thousands, many are innocent thus this project is a call to action to advocate the stop of extrajudicial killings.